Pengaruh Person-Job Fit Terhadap Turnover Intention dengan Work Engagement dan Kepuasan Kerja dalam Etika Bisnis Sebagai Variabel Intervening Studi Pada Karyawan Budget Hotel di Kota Medan - Sitompul, Marthin okuli; Ikhsan, Arfan (Asosiasi Dosen Akuntansi Indonesia, 2025)
One way to manage employees is for companies to implement person-job fit and maintain work engagement and job satisfaction within Business Ethics to ensure employee retention. This is expected to improve employee quality and productivity, leading to growth and prevent turnover intention. This study aims to determine the effect of person-job fit on turnover intention, with work engagement and Business Ethics as intervening variables among budget hotel employees in Medan. This study employed an explanatory research approach with a quantitative approach. The results showed that person-job fit significantly influenced turnover intention, work engagement, and Business Ethics. Work engagement significantly influenced turnover intention, Business Ethics significantly influenced turnover intention, person-job fit significantly influenced turnover intention, mediated by work engagement, and person-job fit significantly influenced turnover intention, mediated by job satisfaction.